FAKTOR-FAKTOR YANG MEMENGARUHI HARGA LAHAN DI KELURAHAN JIMBARAN - Gede Surya Puri Adnyana; Komang Wirawan (Pranatacara Bhumandala: Jurnal Riset Planologi, 2020)
The land price is one of the most dependent impacts on the development of an area, in which the changes in the land price might occur in strategic areas in Indonesia. With the development of the tourism industries, the improvement of academic activities and increasing number of population affected the need for housing in Jimbaran village as well as affecting the annual changes in the land prices. The purpose of this study is to identify the development pattern of the land prices and to identify the factors that influence the changes in the land prices in Jimbaran village. This study was conducted by implementing the quantitative approach. The sampling technique used to select the informants of this study was the purposive sampling method. Methods and techniques of data analysis in this research were used descriptive analysis. Based on the results of the research it was found that (1) the development pattern of the land price at Jimbaran village followed the accessibility path that resulted in a minor peak; (2) the influencing factor, which affected the entirety of the sub-factor area is the distance to academic facilities with the main factor is the availability of the facilities.